Quantifying metabolic energy contributions in sprint running: a novel bioenergetic model - Briand, J.; di Prampero, P. E.; Osgnach, C.; Thibault, G.; Tremblay, J. (European Journal of Applied Physiology, 2025)
Purpose To develop a bioenergetic model representing the dynamics of metabolic power—including aerobic, anaerobic lactic, and anaerobic alactic contributions—during 100-400 m sprints. This study calculates maximum anaerobic capacities using sprint data and assesses the model`s ability to predict performance across various sprint distances.